2021
DOI: 10.1002/clc.23555
|View full text |Cite
|
Sign up to set email alerts
|

Communication approaches to enhance patient motivation and adherence in cardiovascular disease prevention

Abstract: Preventive cardiology visits have traditionally focused on educating patients about disease risk factors and the need to avoid and manage them through lifestyle changes and medications. However, long‐term patient adherence to the recommended interventions remains a key unmet need. In this review we discuss the rationale and potential benefits of a paradigm shift in the clinician‐patient encounter, from focusing on education to explicitly discussing key drivers of individual motivation. This includes the emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
1
14
0
1
Order By: Relevance
“…This supports the idea that brief educational intervention after community-based screening can enhance individual knowledge of CVD risk factors and empower them to seek medical assistance from a primary health care provider. This finding supports the communication approaches "from education to motivation" and personalized communication' to enhance patient motivation and adherence to CVD prevention [33].…”
Section: Discussionsupporting
confidence: 76%
“…This supports the idea that brief educational intervention after community-based screening can enhance individual knowledge of CVD risk factors and empower them to seek medical assistance from a primary health care provider. This finding supports the communication approaches "from education to motivation" and personalized communication' to enhance patient motivation and adherence to CVD prevention [33].…”
Section: Discussionsupporting
confidence: 76%
“…Patient education and information are important and established approaches to ensure and facilitate patient adherence and motivation. 17 According to a recent study, age and educational level are crucial domains for successful implementation of telemedicine. 18 Within TeleCheck-AF, we developed and published standardized instructions that were followed by all participating centres.…”
Section: Assistance In Obtaining Optimal Motivation and Adherencementioning
confidence: 99%
“…In our study, and prior studies, we found a disconnect between patient diagnoses and their own understanding of their pregnancy and future risk related to cardiometabolic disease ( 17 19 , 25 ). Consistent with prior research, participants in our study prioritized the needs of their developing fetuses and babies over their own health ( 17 , 26 ). Effective postpartum counseling may include value-based discussions helping mothers see heart disease prevention as part of caring for their family ( 27 ).…”
Section: Discussionmentioning
confidence: 55%